THE LEGAL PROTECTION OF DATABASES - Viorel ROŞ (Challenges of the Knowledge Society)
The databases are a part of our everyday life and we use them almost without noticing how many and how valuable they are. Without them, our life would be extremely difficult. Just as difficult as a life without computers. There are many advantages that the databases provide to their users: quantity and quality, the ease in identifying the sought information, the possibilities of retrieving the sought information and, last but not least, the user costs, which are much lower than those required for the individual identification of the same information. These are the reasons for which the efforts for creating databases should be compensated by specific means of protection, which ensure both the investment recovery and the expected return and encourage the investments in this field. The lawmaker chose the protection by means of copyright and sui generis right, based on the originality or lack thereof. Below we shall address these means of protection.